Pengaruh Desain Produk, Kualitas Produk dan Citra Merek Terhadap Keputusan Pembelian Produk Erigo - Aldo Norma Bayu Sulistyo (Jurnal Mirai Management, 2023)
The purpose of this study was to examine the effect of work discipline and communication on organizational commitment and job satisfaction as a mediating variable at Budaya Alam Lestari Semarang Company, the study population is all employees of Budaya Alam Lestari Semarang Company in the Central Java area. The sample of this research is 80 employees obtained through the census technique. The data obtained is processed with the SPSS application. The test results stated that work discipline and communication had a significant positive effect on job satisfaction. Work discipline, communication, and job satisfaction have a significant positive effect on organizational commitment. Testing the Sobel test states that job satisfaction can mediate the effect of work discipline on organizational commitment. In addition, job satisfaction can also mediate the effect of communication on organizational commitment. Keywords: Work Discipline, Communication, Organizational Commitment, Job Satisfaction